Laparoscopic versus Open Ladd's Procedure for Intestinal Malrotation in Adults - Frasier, Lane L. (Surg Endosc, 2014)
BACKGROUND: Intestinal malrotation results from errors in fetal intestinal rotation and fixation. While most patients are diagnosed in childhood, some present as adults. Laparoscopic Ladd's procedure is an accepted alternative to laparotomy in children but has not been well-studied in adults. This study was designed to investigate outcomes for adults undergoing laparoscopic Ladd's repair for malrotation. METHODS: We performed a single-institution retrospective chart review over eleven years. Data collected included: patient age, details of pre-operative work-up and diagnosis, surgical management, complications, rates of re-operation, and symptom resolution. Patients were evaluated on an intent-to-treat basis based on their planned operative approach. Categorical data were analyzed using Fisher's exact test. Continuous data were analyzed using Student's T-test. RESULTS: Twenty-two patients were identified (age range 18-63). Fifteen were diagnosed pre-operatively; of the remaining seven patients, four received an intra-operative malrotation diagnosis during elective surgery for another problem. Most had some type of pre-operative imaging, with Computed Tomography being the most common (77.3%). Comparing patients on an intent-to-treat basis, the two groups were similar with respect to age, operative time, and estimated blood loss. Six patients underwent successful laparoscopic repair; three began laparoscopically but were converted to laparotomy. There was a statistically significant difference in length of stay (LOS) (5.0±2.5d vs 11.6±8.1d, p=0.0148) favoring the laparoscopic approach. Three patients required re-operation: 2 underwent side-to-side duodeno-duodenostomy and 1 underwent a re-do Ladd's procedure. Ultimately, 3 (2 laparoscopic, 1 open) had persistent symptoms of bloating (n=2), constipation (n=2), and/or pain (n=1). CONCLUSION: Laparoscopic repair appears to be safe and effective in adults. While a small sample size limits the power of this study, we found a statistically significant decrease in LOS and a trend toward decreased postoperative nasogastric decompression. There were no significant differences in complication rates, re-operation, or persistence of symptoms between groups.